Family planning and reproductive health supply stockouts: problems and remedies for faith-based health facilities in Africa - Amy M. Metzger; Mona Bormet (Health for All Nations, 2017)
Background and aims: Faith-based organizations (FBOs) provide a substantial portion of the health care services in many African countries. FBO facilities do consider family planning and reproductive health services as essential to reducing maternal and child mortality, and to the growth of healthy families. Many health facilities, however, struggle to maintain adequate stocks of reproductive health (RH) supplies because of the various RH supply chains and funding sources, which often operate separately from other medicines and supplies. The purpose of this study is to identify the types of supply chain systems used by African faith-based health facilities to acquire reproductive health products (clotrimazole, combined oral contraceptive pills, contraceptive implants, CycleBeads®, emergency contraception, Erythromycin, female condoms, injectable contraceptives, intra-uterine contraceptive devices, magnesium sulfate, male condoms, Methyldopa, Misoprostol, Nifedpine, Oxytocin, and Progestin-only pills), to describe their problems and challenges, and to identify possible corrective actions. Methods: Through email surveys, phone interviews, and on-site visits, we studied the supply chains of 46 faith-based health facilities in 13 African countries. Sixteen RH commodities, including contraceptives, were selected as indicators. Results: Of the 46 facilities surveyed, 55 percent faced stockouts of one or more products in the three months prior to the survey. Stockouts were less common for contraceptives than for other RH products. Significant strengths of the FBO supply chain included creativity in finding other sources of commodities in the face of stockouts, staff designated to monitor quality of the commodities, high capacity for storage, low incidence of expired products, few instances of poor quality, and strong financial sustainability mechanisms, often including patient fees. Weaknesses included unreliable commodity sources and power supplies, long distances to depots, and problems maintaining the cold chain. Conclusions: By studying the supply chains of faith-based health facilities, Christian Connections for International Health (CCIH) and its members have created new awareness among FBOs and international agencies of the importance and challenges of these systems and have suggested actions toward improvement. The Alliance of Christian Faith-Based Organizations for Family Planning (ACFBOFP) formed in Cameroon to strengthen commodity security may be a good model for other FBOs to consider. Cost recovery models with stronger quantification and forecasting systems, including trained staff, can help meet the FP and RH needs of families and can help assure the long-term sustainability of FBO health systems. This study can serve as a frame of reference as we move forward, anticipating an acceleration in interest to strengthen FBO supply chains to reach as many communities as possible with available, quality supplies and services.